Molecular phylogenetics and species-level systematics of Baylisascaris. Issue 3 (December 2018) - Camp, Lauren E.; Radke, Marc R.; Shihabi, Danny M.; Pagan, Christopher; Yang, Guangyou; Nadler, Steven A.
Abstract: Nucleotide sequences representing nine genes and five presumptive genetic loci were used to infer phylogenetic relationships among seven Baylisascaris species, including one species with no previously available molecular data. These genes were used to test the species status of B. procyonis and B. columnaris using a coalescent approach. Phylogenetic analysis based on combined analysis of sequence data strongly supported monophyly of the genus and separated the species into two main clades. Clade 1 included B. procyonis, B. columnaris, and B. devosi, species hosted by musteloid carnivores. Clade 2 included B. transfuga and B. schroederi from ursids, B. ailuri, a species from the red panda (a musteloid), and B. tasmaniensis from a marsupial. Within clade 2, geographic isolates of B. transfuga, B. schroederi (from giant panda), and B. ailuri formed a strongly supported clade. In certain analyses (e.g., some single genes), B. tasmaniensis was sister to all other Baylisascaris species rather than sister to the species from ursids and red panda. Using one combination of priors corresponding to moderate population size and shallow genetic divergence, the multispecies coalescent analysis of B. procyonis and B. columnaris yielded moderate support (posterior probability 0.91) for these taxa as separate species. However, other prior combinations yielded weak or no support for delimiting these taxa as separate species. Similarly, tree topologies constrained to represent reciprocal monophyly of B. columnaris and B. procyonis individuals (topologies consistent with separate species) were significantly worse in some cases, but not others, depending on the dataset analyzed. An expanded analysis of SNPs and other genetic markers that were previously suggested to distinguish between individuals of B. procyonis and B. columnaris was made by characterization of additional individual nematodes. The results suggest that many of these SNPs do not represent fixed differences between nematodes derived from raccoon and skunk hosts. Graphical abstract: Image 1 Highlights: A phylogenetic hypothesis for Baylisascaris species was produced using nine genes. Genetic data was generated for two new species- B. devosi and B. tasmaniensis . Baylisascaris devosi and B. tasmaniensis were part of a monophyletic Baylisascaris . B. procyonis (raccoon) and B. columnaris (skunk) could not be reliably distinguished. Established SNPs may not be diagnostic for Baylisascaris from raccoons and skunks.